AKUNTANSI DAN PENGELOLAAN DANA DESA (STUDI KASUS DESA SUNGAI GELAM KECAMATAN SUNGAI GELAM KABUPATEN MUARO JAMBI - Arna Suryani (Universitas Batanghari, 2018)
This research aims to provide insight to the village authorities about the problems that plagued the village related to accounting and financial management of the village Fund. Research conducted in the village of Sungai Gelam Sub River Gelam Muaro Jambi Regency. Types of data used in this research is the primary data and secondary data. The method of data collection is carried out triangulation (combined), namely in the form of observations (observation), interview (interview), the library (library reaserch), and documentation (documentation). This research is descriptive research using qualitative approach with an analysis of inductive or qualitative in nature. This research seeks mendiskripsikan a clear picture of the phenomena that occur in the application of accounting and financial management of the village. The results showed all transactions that originate from the village Fund Allocation has been recorded using a recording system of accountancy assisted by computer using the Microsoft Excel program. Mechanism of liquefaction of sources of income of the village, including the allocation of Funds that were in accordance with the rules of Regent Muaro Jambi Number Number 17 in 2015 about an Ordinance Division and assignment details the village Fund. The stages of preparation of the financial management of the allocation of the funds of the village starts from planning, deployment, and accountability and reporting have been referring to the Regulations the Regents Muaro Jambi 2015 15 years of Regulatory Guidelines for financial management of the village. To overcome the obstacles faced in the implementation of accounting and financial management of the allocation of funds in the village of Sungai Gelam village development activities against mainly sourced from the village Fund Allocation minimal Socializing, parties should the Government further promotes the village to the community about the latest programs and provide a grace period to understand about the new programs. The role of the community is necessary for the two sides to the good Government of the village as well as the society for mutual cooperation, provide motivation, and knowledge toward the critical role community as trustees so that it can create positive feedback. Coaching through guidance-guidance techniques specifically and routinely socialization can be done to improve the skills of Human Resources in understanding the accounting and record-keeping system for financial management of the allocation of Funds.